The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00426-019-01163-9
|View full text |Cite
|
Sign up to set email alerts
|

Silent shapes and shapeless sounds: the robustness of the diminished crossmodal correspondences effect in autism spectrum conditions

Abstract: We performed a registered replication of the Oberman and Ramachandran (Soc Neurosci 3(3-4):348-355, 2008) study on the 'kiki/bouba' effect in autism spectrum conditions (ASC). The aim of the study was to test the robustness of the diminished crossmodal correspondences effect in autism, but also to verify whether this effect is not an artifact of differences in intelligence. We tested a Polish-speaking sample of 21 participants with ADOS-confirmed autism spectrum conditions (mean age 15.90) and 21 age-(mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…Here, we observed that our participants with higher AQ scores tended to make fewer of the consensual color–taste/shape–color associations, suggesting that the autistic traits play a role in constructing crossmodal correspondences. This result was consistent with previous findings that individuals with autism showed atypical sensory processing and deficits in binding sensory information across modalities ( Oberman and Ramachandran, 2008 ; Foss-Feig et al, 2010 ; Cascio et al, 2012a ; Kujala et al, 2013 ; Occelli et al, 2013 ; Visser et al, 2013 ; Stevenson et al, 2014b , 2016 ; Wada et al, 2014 ; Gold and Segal, 2017 ; Król and Ferenc, 2020 ; Yaguchi and Hidaka, 2020 ), as evident in audio–visual processing ( Gelder et al, 1991 ; Mongillo et al, 2008 ; Irwin et al, 2011 ; Collignon et al, 2013 ; Bebko et al, 2014 ; Stevenson et al, 2014b ; Hidaka and Yaguchi, 2018 ), audio–tactile processing ( Russo et al, 2010 ), and visual–tactile processing ( Cascio et al, 2012a ; Noel et al, 2020 ). For example, Occelli et al (2013) found that children with ASD showed lower proportion of expected takete–maluma associations, and the performance varied as a function of the severity of the symptomatology.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here, we observed that our participants with higher AQ scores tended to make fewer of the consensual color–taste/shape–color associations, suggesting that the autistic traits play a role in constructing crossmodal correspondences. This result was consistent with previous findings that individuals with autism showed atypical sensory processing and deficits in binding sensory information across modalities ( Oberman and Ramachandran, 2008 ; Foss-Feig et al, 2010 ; Cascio et al, 2012a ; Kujala et al, 2013 ; Occelli et al, 2013 ; Visser et al, 2013 ; Stevenson et al, 2014b , 2016 ; Wada et al, 2014 ; Gold and Segal, 2017 ; Król and Ferenc, 2020 ; Yaguchi and Hidaka, 2020 ), as evident in audio–visual processing ( Gelder et al, 1991 ; Mongillo et al, 2008 ; Irwin et al, 2011 ; Collignon et al, 2013 ; Bebko et al, 2014 ; Stevenson et al, 2014b ; Hidaka and Yaguchi, 2018 ), audio–tactile processing ( Russo et al, 2010 ), and visual–tactile processing ( Cascio et al, 2012a ; Noel et al, 2020 ). For example, Occelli et al (2013) found that children with ASD showed lower proportion of expected takete–maluma associations, and the performance varied as a function of the severity of the symptomatology.…”
Section: Discussionsupporting
confidence: 93%
“…The impaired ability to integrate multisensory information in individuals with ASD may arise from an underlying impairment in perceiving the relationships between cross-modal inputs ( Stevenson et al, 2014a ). For example, the most studied “bouba–kiki” effect (i.e., people associate rounded shapes with words like “bouba” or “maluma,” and spiky shapes with words like “kiki” or “takete”; Köhler, 1947 ) was reported to be less pronounced in individuals with autism compared to controls ( Oberman and Ramachandran, 2008 ; Occelli et al, 2013 ; Gold and Segal, 2017 ; Król and Ferenc, 2020 ). Oberman and Ramachandran (2008) found that children with ASD do not show the “bouba–kiki” effect that neurologically typical adults and children show (the neurotypical children chose expected sound–shape associations 88% of the time, while children with ASD chose only 56% of the time, compared to the chance of 50%).…”
Section: Introductionmentioning
confidence: 99%
“…The research that has been published to date shows that those scoring high on the autism spectrum appear to be less sensitive to certain of the correspondences that have been demonstrated in the normal population, such as, for example, the so-called bouba-kiki effect (e.g., Gold and Segal, 2017;Król and Ferenc, 2020;Stewart et al, 2016). In one of the first studies of its kind to document such individual differences, Oberman and Ramachandran (2008) provided some preliminary evidence for a reduced strength of cross-modal correspondences in a group of 10 individuals with autism spectrum disorder (ASD).…”
Section: Autism Spectrum and Individual Differences In Cross-modal Co...mentioning
confidence: 99%
“…Moreover, individuals with ASD have been shown to exhibit impaired multisensory integration and show less pronounced crossmodal correspondences. For example, the well-known "Bouba-Kiki" effect (i.e., people associate rounded shapes with words like "bouba" or "maluma," and spiky shapes with words like "kiki" or "takete"; Köhler, 1947) was weaker in individuals with ASDs than in controls (Gold & Segal, 2017;Król & Ferenc, 2020;Oberman & Ramachandran, 2008;Occelli et al, 2013). Chen et al (2021) reported that individuals with higher autistic traits showed fewer consensual color-taste (e.g., yellow-sour taste) and CSAs using a questionnaire survey.…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 99%